Implementasi E-Commerce sebagai Media Penjualan Online pada Toko Athena Shop - Ainun Jakia Ritonga; Zuhrinal M. Nawawi (Economic Reviews Journal, 2022)
E-commerce is the act of buying and selling through electronic media related to the internet. Athena Shop is a specialty shop that specializes in baby goods such as feeding, sleeping and dressing items. The last few months have seen a decline in sales in Athens stores. This is because e-commerce is growing in popularity, making it difficult for offline businesses like Athena Shop to compete with them because it provides so many advantages for both buyers and sellers. The implementation of e-commerce with wordpress content management system (CMS) as an online sales platform at the Athena store is one option to overcome this problem. Thanks to e-commerce, Athena Shop can compete in the baby gear market and boost sales. E-commerce has removed the requirement for customers to physically visit stores to make purchases. E-commerce can also make it easier to find out the latest information about the latest products. In addition, it makes it easy for merchants to understand all things related to bestseller reports, price reductions, product shipping, refunds and returns. Keywords: Implementation, internet, E-commerce, online shop, baby shop.